2022
DOI: 10.21873/anticanres.16035
|View full text |Cite
|
Sign up to set email alerts
|

Significant Contribution of Interleukin-18 Genotypes to Childhood Acute Lymphocytic Leukemia Risk in Taiwanese

Abstract: Background/Aim: Evidence has shown that has both antitumor and pro-tumor effects in various types of leukemia. The current study aimed at investigating the contribution of IL-18 polymorphisms to the risk of childhood acute lymphocytic leukemia (ALL) in Taiwan. Materials and Methods: IL-18 promoter -656 (rs1946519), -607 (rs1946518), and -137 (rs187238) genotypes of 266 childhood ALL cases and 266 controls were determined by polymerase chain reaction-restriction fragment length polymorphism methodology. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…From the results, Saadi et al [ 19 ] suggested that IL18 is an important prognostic marker in AML and control of the expression and regulation of IL18 may play key roles in the management of AML. Chen et al [ 21 ] showed that overexpression of IL18 might reflect the convergence of several important unfavorable prognostic factors in AML. Song et al [ 22 ] also suggested that high circulating levels of IL18 are a potential predictor for a decreased risk of AML.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, Saadi et al [ 19 ] suggested that IL18 is an important prognostic marker in AML and control of the expression and regulation of IL18 may play key roles in the management of AML. Chen et al [ 21 ] showed that overexpression of IL18 might reflect the convergence of several important unfavorable prognostic factors in AML. Song et al [ 22 ] also suggested that high circulating levels of IL18 are a potential predictor for a decreased risk of AML.…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping design and settings. Genomic DNA from each participant was isolated from peripheral blood leukocytes using a QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan, ROC) and stored in aliquots, as previously described (11,12,30,31). Table I provides a summary of information about the polymorphic sites, forward and reverse primers, restriction enzymes, and polymerase chain reaction (PCR) fragment sizes following enzyme digestion, along with references from the literature (28,(32)(33)(34)(35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%